Exploring TPACK Barriers of EFL Junior High School Pre-service Teachers: Narrative Inquiry - Jamila, Siti; Basya, Dihliza (Linguapedia, 2024)
Technology, content, and pedagogy must have a meaningful relationship with each other so that Pre-service English Teachers' literacy can be connected to a variety of semiotic modes beyond written language. Interaction with a greater variety of texts in a variety of modes, media, and environments highlights the need for tools to assess English language instructors' TPACK when it comes to educating students in multimodal literacy. Several pre-service English teachers in EFL classes utilize the use of word wall media for learning. This research aims to identify the obstacles faced by pre-service teachers in utilizing TPACK to teach EFL English at a private university in East Java, Indonesia. By adapting the interview framework (Creswell, 2018), which consists of four discussion targets, including pre-service teachers' beliefs regarding the practice of using TPACK, which is applied in learning activities in junior high schools. This narrative qualitative method (Clandinin & Connelly, 2000) uses semi-structured interviews as its instrument. Systematically using Widodo's (2014) thematic analysis to analyze qualitative data. The findings show that there are many obstacles faced by pre-service teachers and students in implementing learning using TPACK in EFL classes, to be effective for their future teachers, pre-service skills.